Kesalahan Siswa dalam Menyelesaikan Soal HOTS Ditinjau dari Metakognisi di MTsN 1 Mataram - Hanifa Zahrani; Sri Subarinah; Ulfa Lu’luilmaknun (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The ability of students to solve Higher Order Thinking Skills (HOTS) problems in mathematics remains low,leading to frequent errors during problem-solving processes. Differences in the types of errors made bystudents based on their metacognitive levels have also not been widely examined in depth. This study aimsto describe Newman’s types of errors based on students’ metacognitive levels in solving HOTS questions onthe Pythagorean Theorem. This research employed a descriptive qualitative approach involving 32 ninthgradestudents of class IX.1 at MTsN 1 Mataram in the 2025/2026 academic year. The instruments usedincluded a metacognitive skills questionnaire, a HOTS-based written test, and interview guidelines. Theresults show that students with high metacognitive levels tended to make errors in the transformation,process skills, and encoding stages. Students with moderate metacognitive levels made errors from thecomprehension to the transformation stages, while students with low metacognitive levels made errors inalmost all stages of Newman’s procedure. This study concludes that the lower the students’ metacognitivelevel, the higher the frequency and variety of errors that appear when solving HOTS problems.